DESIGNING HOTEL SERVICES TO INCREASE THE SUSTAINABILITY OF HOSPITALITY INDUSTRY INSTITUTIONS - Піддубний, Володимир; Тарасюк, Галина; Чагайда, Андрій; Радченко, Юрій (SWorldJournal, 2024)
The paper examines the impact of hospitality industry establishments on the environment and ways to reduce emissions and reduce energy consumption. In general, most institutions implement low-cost environmental strategies, such as energy management, wast